Anti-diabetic effects of fullerene C60 nanoparticle mediated by its anti-oxidant activity in the pancreas in type 1 diabetic rats - Zahra Bahari; Mehri Farhang Ranjbar; Fariba Namdar; Mohammad Ehsan Bayatpoor; Mohammad Taghi Mohammadi (Universidade de São Paulo, 2023)
Abstract The present study aims to examine the anti-diabetic effects of fullerene C60 nanoparticle, as an anti-oxidant compound, on serum glucose level, body weight, food and water intake, and pancreatic oxidative stress in the rats with type 1 diabetes. Diabetes mellitus was induced by single intravenous injection of streptozotocine (45 mg/kg) into the tail vein of the rats. Four groups of rats were divided as follow: normal, normal treatment, diabetic, and diabetic treatment groups. Normal treatment and diabetic treatment groups received intra-orally fullerene (1 mg/ kg/daily) up to day 60 following streptozotocine injection. Oxidative stress markers in the pancreas were evaluated on day 60 after inducing diabetes mellitus. Injection of streptozotocine significantly increased serum glucose level as well as food and water intake on all experimental days; it decreased body weight on day 60. Streptozotocine increased MDA level and decreased GSH level and SOD activity in the pancreas. Fullerene significantly decreased food and water intake and increased body weight as compared with the diabetic group. Fullerene also could normalize the pancreatic MDA and GSH markers. The present study suggested that fullerene can decrease diabetic symptoms via its anti-oxidant activity in the pancreas in the rats with type 1 diabetes mellitus.